PUSAT OLAHRAGA PANJAT TEBING DI BANJARBARU - Suparman, Farras Nabila; Heldiansyah, J.C. (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
ABSTRACT Rock climbing is a sport that is not foreign in Indonesia, but Federasi Panjat Tebing Indonesia (FPTI) says that the facilities in Banjarbaru are still underdeveloped. These inadequate and unattractive facilities are the cause of the lack of public awareness of this sport even though the sport is starting to develop rapidly. Athletes who have succeeded in winning several national championships face difficulties due to the lack of proper facilities, the general public also cannot try this sport for those who are interested in it as recreation or just want to doing it as a hobby without having to join a certain organization or having to travel quite a long distance to do rock climbing on natural mountains. For this reason, a rock climbing sports center that meets the standards and is recreational is needed in Banjarbaru. The design of the rock climbing center in Banjarbaru uses Contemporary Architecture as the methods and with adaptive space concepts where the space, circulation and furnitures in the building adapts to various activities so that they can take place at the same time and increasing social interaction.